The Effect of Using The Direct Method with Question Ball Media to Improve Students' Speaking Skill / Atsar Istikhdaam Thariqah al-Mubasyirah Bi Wasilah La’b Kurrah al-Asilah Li Tarqiyyah Maharah al-Kalam ‘inda ath-Thullab - Kamal, Musthafa; Mukarom, Arik Maghfirotul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Based on the results of preliminary study and interviewing Arabic language teachers, it was found that the student's competency in class VII at Pondok Pesantren Assalam (Assalam Boarding School) of Naga Beralih in Kampar Utara was relatively weak; and they were afraid to speak or to perform storytelling and dialogue. Then, if they do a dialogue, they will not be able to do it fluently yet. The research was carried out in an experimental design that requires an experimental class and a control class. The sample was 40 students who were randomly assigned to the experimental class and the control class. The instruments for collecting the data were (1) an observation sheet, (2) a test, and (3) documentation. The obtained data were analyzed by using SPSS Statistics, Version18. The research results showed that (1) the implementation Mubasyaroh method by using Question Ball Media was very well with a percentage of 95%, (2) based on the results of the tests, Ha was accepted, consequently, Ho was rejected which results greater than ttable (2.745 >2.02), (3) Direct method by using Question Ball Media had a significant influence on the students' speaking skills. The factors that affected the student's proficiency were (1) the suitability of the teaching method with the learned materials, (2) the use of media in the teaching and learning process, (3) the expertise of teachers in selecting the teaching method, (4) teachers' activeness in innovating the method and media, (5) the appropriateness of teaching materials with the students level, and(6) the teacher preparation to carry out the teaching and learning process.